Pembentukan Tim Pendamping Literasi Daerah dan Penguatan Literasi di Kabupaten Bengkulu Utara - Gumono, Gumono; Sarwono, Sarwit; Yulistio, Didi; Trianto, Agus; Utomo, Bayu (Edumedia Solution, 2024)
This activity aims to manifest Bengkulu University's participation in accelerating the increase in community literacy, especially in the District Bengkulu Utara, Bengkulu Province. Bearing in mind that the results of various surveys and evaluations of the GLN program in North Bengkulu show that the implementation of movement and literacy skills could have been better. This community service is conducted through counseling and focus group discussions to equalize perceptions and form a District Regional Literacy Assistance Team—North Bengkulu to share their role in making GLN a success. The activity was held on August 30, 2022, inviting the Regional Government/Regional Government, District Education Office, Regional Library and Archives Service, Regional Planning and Development Agency (Bappeda), Professional Organizations (MGMP), Academics, and Regional Policy Stakeholders. However, the only participants present were academics, teachers from MGMP elements, and the sub-district head. The analysis results show that strengthening literacy has not become a shared responsibility. Policymakers and stakeholders still think that strengthening literacy skills is the responsibility of schools (teachers) alone. TPLD has not been successfully formed for this activity because parties in the field of literacy have not fully attended it.